The socio economic effect of cancer on patients’ livelihoods in Kenyan house holds - Mutuma, J; Wakhungu, J; Mutai, C (BIBECHANA, 2016)
The study assessed The socio economic effect of cancer on patients’ livelihoods in kenyan households. In Kenya, cancer is ranked third among the main causes of death after infectious and cardiovascular diseases. In recent years, cases of cancer in Kenya have increased creating a burden on many households. This has negatively impacted on poverty alleviation and sustainable development in the long run. A Sample of 245 patients seeking treatment in the three major oncology centers in the country namely Kenyatta National and Referal Hospital, Moi Teaching and Referal Hospital and Agakhan University Hospital was used. Data was collected through self-administered questionares, Focus groups discussions and key informant interviews. A triangulation approach involving in-depth interview using questionnaires as the main collection instrument for key informants were carried out. Secondary data was collected through case study, review of documents, reports and publications related to the topic and online journals. Chi square was used to test the independence of variables. The result revealed poverty, late and poor cancer diagnosis and lack of medical cover were found to be the top ranking serious challenges facing cancer patients in the country. Cross-sectional survey, correlational and evaluation research designs were adopted for the study. Both non-probability sampling and probabilistic sampling methods were used in selecting subjects seeking treatment at the three main oncology centers in Kenya. BIBECHANA 14 (2017) 37-47